2008
DOI: 10.1123/apaq.25.3.247
|View full text |Cite
|
Sign up to set email alerts
|

Activity Levels during Physical Education and Recess in Two Special Schools for Children with Mild Intellectual Disabilities

Abstract: This study compared physical education (PE) and recess in two markedly different special schools for children with mild intellectual disabilities; one school had a reputation for focusing on sports (High Sport Focus-HSF) and the other did not (Low Sport Focus-LSF). Data were collected in 24 PE classes and 48 recess periods using a validated observation system. During both PE and recess, HSF students engaged in physical activity (PA) at greater intensity levels, but LSF students accrued more total activity min.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 31 publications
0
18
0
2
Order By: Relevance
“…In this research, the participants tended to generate greater PA on the days when they attended school, although their average normal step counts on weekdays were still lower than that of the recommended. School policies have been shown to influence PA habits of children in special schools (Sit, McKenzie, Lian, & McManus, 2008), and it is possible that school programming generates a more active routine among children on weekdays. Hence, it is likely that weekday PA could be enhanced if schools provide PA programs systematically.…”
Section: Discussionmentioning
confidence: 99%
“…In this research, the participants tended to generate greater PA on the days when they attended school, although their average normal step counts on weekdays were still lower than that of the recommended. School policies have been shown to influence PA habits of children in special schools (Sit, McKenzie, Lian, & McManus, 2008), and it is possible that school programming generates a more active routine among children on weekdays. Hence, it is likely that weekday PA could be enhanced if schools provide PA programs systematically.…”
Section: Discussionmentioning
confidence: 99%
“…However, the literature focusing on this topic is very sparse [8,18,19]. Parrish et al [8] have investigated PA between schools from lower and average SES areas.…”
Section: Discussionmentioning
confidence: 99%
“…Kwan, et al [78], reported a direct association between motivation and PA involvement in children with developmental coordination disorder. Sit, et al [83], found greater involvement in PA during recess (more autonomous) compared to PE instruction (less autonomous) in a sample of children with ID. McLoughlin, et al [79], attributed the involvement in sports participation to the self-determination motives for athletes with physical disabilities and noted that specific barriers (e.g.…”
Section: Discussionmentioning
confidence: 96%